Antibiotic-Resistant Infections Among Inpatients with Coronavirus Disease 2019 (COVID-19) in US Hospitals . (2nd July 2022) - Baggs, James; Rose, Ashley N; McCarthy, Natalie L; Wolford, Hannah; Srinivasan, Arjun; Jernigan, John A; Reddy, Sujan C
Abstract: We described bacterial/fungal coinfections and antibiotic-resistant infections among inpatients with a diagnosis of coronavirus disease 2019 (COVID-19) and compared findings in those with a diagnosis of influenza like illness. Less than 10% of inpatients with COVID-19 had bacterial/fungal coinfection. Longer lengths of stay, critical care stay, and mechanical ventilation contribute to increased incidence of hospital-onset infections among inpatients with COVID-19.